2014
DOI: 10.1021/np500276c
|View full text |Cite|
|
Sign up to set email alerts
|

Complete Stereochemistry and Preliminary Structure–Activity Relationship of Rakicidin A, a Hypoxia-Selective Cytotoxin from Micromonospora sp.

Abstract: The complete stereochemistry of rakicidin A, a hypoxia-selective cytotoxin produced by Micromonospora sp., was unambiguously established by extensive chemical degradation and derivatization studies. During the PGME derivatization-based configurational analysis of 3-hydroxy-2,4,16-trimethylheptadecanoic acid, an irregular Δδ distribution was observed, which necessitated further acylation of the 3-hydroxy group to resolve the inconsistency. A hydrogenated derivative of rakicidin A, its ring-opened product, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Further, each tested compound displayed different potency on each inflammatory factor due to its structural difference, although they all possess same basic skeleton. It indicated that 3D-strcuture is very important in the bioactivity [ 45 , 46 , 47 , 48 , 49 ]. Taken together from PCA, the structural similarity between 2 and 3 is relatively higher than that of the others, and they displayed better effects against IL-1 ß , IL-6 and PGE2 than the others.…”
Section: Resultsmentioning
confidence: 99%
“…Further, each tested compound displayed different potency on each inflammatory factor due to its structural difference, although they all possess same basic skeleton. It indicated that 3D-strcuture is very important in the bioactivity [ 45 , 46 , 47 , 48 , 49 ]. Taken together from PCA, the structural similarity between 2 and 3 is relatively higher than that of the others, and they displayed better effects against IL-1 ß , IL-6 and PGE2 than the others.…”
Section: Resultsmentioning
confidence: 99%
“…This analyses converged upon (2 R , 3 R , 14 R , 15 R , 16 S ) as the most likely configuration of natural rakicidin A, and we initially targeted this particular isomer. Recently, two reports appeared, both claiming assignment of the configuration of rakicidin A . Through synthesis of a compound with spectroscopic data matching those of the natural product, Chen and co‐workers arrived at a (2 S , 3 S , 14 S , 15 S , 16 R ) configuration, whereas Igarashi and co‐workers paradoxically concluded the stereochemistry to be (2 R , 3 R , 14 S , 15 S , 16 R ) by direct degradation of the natural product and comparison with authentic standards (Figure A) .…”
Section: Figurementioning
confidence: 99%
“…Recently, two reports appeared, both claiming assignment of the configuration of rakicidin A . Through synthesis of a compound with spectroscopic data matching those of the natural product, Chen and co‐workers arrived at a (2 S , 3 S , 14 S , 15 S , 16 R ) configuration, whereas Igarashi and co‐workers paradoxically concluded the stereochemistry to be (2 R , 3 R , 14 S , 15 S , 16 R ) by direct degradation of the natural product and comparison with authentic standards (Figure A) . This latter assignment, however, was corrected earlier this year to corroborate a (2 S ,3 S ,14 S ,15 S ,16 R ) configuration for rakicidin A, and it was thus clear that our initial synthesis in fact had targeted ent ‐rakicidin A. Herein, we report our unique route to the natural isomer of rakicidin A, along with biological evaluation and the discovery of a simplified bioactive rakicidin A analogue.…”
Section: Figurementioning
confidence: 99%
“…Recently,t wo reports appeared, both claiming assignment of the configuration of rakicidin A. [13,14] Through synthesis of ac ompound with spectroscopic data matching those of the natural product, Chen and co-workers arrived at a( 2 S,3S,14S,15S,16R)c onfiguration, [13] whereas Igarashi and co-workers paradoxically concluded the stereochemistry to be (2R,3R,14S,15S,16R)b yd irect degradation of the natural product and comparison with authentic standards ( Figure 1A). [14] This latter assignment, however, was corrected earlier this year to corroborate a( 2 S,3S,14S,15S,16R) configuration for rakicidin A, and it was thus clear that our initial synthesis in fact had targeted ent-rakicidin A. Herein, we report our unique route to the natural isomer of rakicidin A, along with biological evaluation and the discovery of asimplified bioactive rakicidin Aanalogue.…”
mentioning
confidence: 99%